Interculturality and International Information. The big challenge in the Mixed Century - Travesedo de Castilla, Concepción (Historia y Comunicación Social, 2014)
Studies on international communication and intercultural communication share common intellectual roots, career and epistemological bases. Both are also related to major global social dilemmas, and have implications in activism and social change. One of the main challenges in this mixed century, faced with the advent of an information space progressively open to all cultures and civilizations, is to ensure intercultural dialogue.